The Effect of Leadership And Conflict on Performance of Education Services of Buton District - Anco Anco; Apipudin Apipudin; Muhammad Arifin (International Journal of Social Service and Research, 2021)
The object of this research is to obtain information about the effect of leadership and conflict on performance. It was quantitative research with survey method in Buton District Educational Officer. The research was conducted to all lecturer of The Buton District Educational Officer.  by using a survey method with path analysis applied in testing hypothesis. There is 73 employees are used as a sample was selected by using Slovin formula. The research conlude: (1) There is a direct positive effect of leadership on performance. (2) There is a direct negative effect of conflict on performance. (3) There is a direct negative of leadership on conflict